Implementasi Pengelolaan Lembaga Amil Zakat Pada Yayasan Yatim Mandiri Surabaya - Nadya Irmania; Achsania Hendratmi (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
This purpose of this research is to know the implementation of amil zakah institution controlling management in amil zakah institution Surabaya using planning, organizing, actuating and controlling management and a leads to orphans.This research used qualitative approach with case study method. The subject of this research would be the informants that give informations needed. The Informants were determined by purposive sampling technique purposive sampling is a technique to determine the samples intentionally and also depend on current consideration. The result of this research showed that the implementation of amil zakah institution controlling management has fitted to planning, organizing, actuating, and controlling management. Education, economy, and health are the important points that need to be considered in an attention to orphans.Amil zakah institution needs an achnowledged standart of social service givings it’s about the ways to do social service activities, human resources, facilities and social service administration by alternative minimum, indicative, and maximum standart for each services.